Case Report: Ultrasonography and Magnetic Resonance Imaging of Anterior Segment Dysgenesis in a Calf - Tsuka, Takeshi; Okamoto, Yoshiharu; Sunden, Yuji; Morita, Takehito; Amaha, Takao; Ito, Norihiko; Murahata, Yusuke; Yamashita, Masamichi; Osaki, Tomohiro; Imagawa, Tomohiro (Frontiers in Veterinary Science, 2022)
A 7-day-old male Holstein calf presented with progressive unilateral exophthalmos associated with enlargement of the right eyeball soon after birth. Ultrasonography of the enlarged right eyeball showed 1) a 2-cm-thick echogenic parenchymal lesion filling the anterior region of the right eyeball, 2) excess accumulation of the anechoic vitreous humor, and 3) absence of the lens structure. Antemortem examination using T2-weighted and ﬂuid-attenuated inversion recovery magnetic resonance imaging (MRI) revealed a thickened, hyperintense anterior lesion and absence of the lens structure. These imaging findings were suggestive of anterior segment dysgenesis. Antemortem imaging showed no abnormalities other than the abnormal structure and size of the right eyeball; therefore, enucleation of the right eye was performed, which allowed intact healing without suppuration. To the best of our knowledge, this is the first case report describing the antemortem application of ultrasonography and MRI for the diagnosis of anterior segment dysgenesis in a Holstein calf. Ocular ultrasonography enhanced the diagnostic accuracy due to the characteristic ultrasonographic findings of a thickened anterior lesion and absence of the lens structure in the eyeball, suggestive of anterior segment dysgenesis.